Islamic Educational Values in The Marriage Tradition of The Banjar Ethnic Community in Teluk Sialang Village - Abd. Hamid; Ari Susanto; Kholilullah Kholilullah (Assyfa Journal of Islamic Studies, 2026)
This study aims to determine the Islamic educational values in the implementation process of the Banjar ethnic marriage tradition in Teluk Sialang Village, Tungkal Ilir District, West Tanjung Jabung Regency. The problems in this study are to find out how the marriage tradition of the Banjar ethnic community is and to find out the Islamic educational values in the Banjar ethnic marriage tradition. This research is a field research. Data collection was carried out using observation, interview and documentation methods. This research was analyzed using data reduction, data presentation and verification. The findings of this study are: 1) the marriage traditions of the Banjar ethnic community include: (a) Basasuluh (investigating), (b) Batatakunan, (c) Badatang/Bapara (proposing), (d) Bapayuan/Bapatut Jujuran (determination of dowry), (e) Maatar Jujuran/Patalian (engagement), (f) Bapingit (seclusion), (g) Bapacar (henna), (h) Badudus/Bapapai, (i) Marriage Contract, (j) Batamat (Khatam Qur'an), (k) Ma'arak Pengantin (bridal procession), (l) Bersanding/Batatai Tradition; 2) the Islamic educational values in the Banjar ethnic marriage tradition include: (a) faith values, (b) worship values, (c) moral values, (d) silaturrahmi values.